Assessment of health worker knowledge in fistula management in Uganda - Kanakulya, H; Ndwiga, C; Sripad, P; Arnoff, E; Mukisa, R; Warren, S; Barageine, J (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To assess knowledge, attitudes, and practices related to female genital fistula among Primary Health Care (PHC) providers in Uganda. Methods: A structured questionnaire was administered to purposively sampled PHC providers, data were collected using the ODK mobile technology platform and analyzed using Stata 13.1 software. Results: 114 PHC providers (62 Masaka, 52 Kalungu) in 50 health centers (28 level II, 18 level III and 4 level IV) were assessed. Findings showed that 57% could define prolonged labor correctly; almost none knew that leaking faeces and urine was a postnatal fistula sign/symptom. 28% reported having seen patients that leaked urine uncontrollably. 24% reported having seen clients fistula symptoms, 39% knew that fistula clients should be counseled and referred for treatment, and 25% had ever referred clients who leak urine. Conclusions: PHC providers lacked adequate knowledge of fistula and related issues. If PHC providers are to be engaged in fistula screening and referral, this topic must be integrated into the training curriculum. Conversely, it may be important to provide women with direct access to information on referral and treatment of fistula.